The book of F♯ : breaking free with managed functional programming - Fancher, Dave (No Starch Press, 2014)
F♯ brings the power of functional-first programming to the .NET Framework, a platform for developing software in the Microsoft Windows ecosystem. If you're a traditional .NET developer used to C♯ and Visual Basic, discovering F♯ will be a revelation that will change how you code, and how you think about coding. In The Book of F♯, Microsoft MVP Dave Fancher shares his expertise and teaches you how to wield the power of F♯ to write succinct, reliable, and predictable code. As you learn to take advantage of features like default immutability, pipelining, type inference, and pattern matching, you'l.